ANALISIS PENGALAMAN PENGGUNA APLIKASI ROBLOX DITINJAU DARI PERSPEKTIF MODEL KUALITAS MCCALL - Vania Wafiq Azizah; Amelia Balqis; Aisyah Lutfi Sarahma; Ulfi Nur Islamiyati; Dendy Kurniawan (Jurnal Riset Sistem Informasi, 2026)
Roblox is a multi-purpose online gaming platform used by more than 70 million users daily. Despite its popularity, there are still user complaints related to application performance, such as lag, frame rate drops, system instability, and difficulties in using the application across various devices. This study aims to analyze the user experience of the Roblox application from the perspective of the McCall Quality Model, which includes five main factors: correctness, reliability, efficiency, usability, and integrity. This research employs a descriptive quantitative approach by collecting data through an online questionnaire distributed to 67 active Roblox users. The questionnaire instrument was developed based on indicators of the McCall Model and utilized a Likert scale to measure user perceptions. The data were analyzed descriptively by calculating the mean and percentage for each quality factor. The results indicate that the overall quality of the Roblox application falls into the “Good” category, with an average score of 72.6%. The usability factor achieved the highest score at 77.8% (Very Good), indicating that the application is easy to use. Meanwhile, the reliability factor obtained the lowest score at 69.0% (Good), suggesting that issues related to system stability still exist. These findings indicate that although the Roblox application demonstrates good quality from the user’s perspective, improvements are still needed in terms of performance and efficiency, particularly for mobile devices with lower specifications.